The effect of gelatine packaging film containing a Spirulina platensis protein concentrate on atlantic mackerel shelf life - Stejskal, Nadia (2020)
The use of packaging films containing natural preservative compounds attracts great attention for the quality improvement of seafood. Microalga spirulina (Spirulina platensis) represents a potential source of high added-value and preservative biocompounds. The goal of this study was to enhance the quality of refrigerated Atlantic mackerel (Scomber scombrus) by including a protein concentrate (PC) of spirulina in a gelatine-based film. Quality changes in fish muscle were monitored by microbial and chemical analyses throughout an 11-day refrigerated storage (4 °C). As a result of the presence of spirulina PC in the film, an antimicrobial effect (p < 0.05) was concluded as determined by comparative evolution of aerobes and psychrotrophs, while no effect (p > 0.05) was concluded for Enterobacteriaceae, proteolytics and lipolytics counts. Furthermore, a lower (p < 0.05) formation of trimethylamine and free fatty acids was detected. Lipid oxidation, measured by fluorescent compounds formation, also exhibited lower average values in fish corresponding to the batch containing spirulina concentrate. The preservative effects observed can be explained on the basis of the presence of antimicrobial and antioxidant compounds in the microalga concentrate. It is proposed that the current packaging system may constitute a novel and promising strategy to enhance the quality of commercial refrigerated fatty fish.